(untitled) (Research, Society and Development, 2020)
The frontier is an object of research, considering that different relations are established in it. In addition, the frontier becomes even more interesting because it is possible to observe it from different perspectives, which can complement or even oppose each other. Thus, the objective of the study is to present observations and reflections made from the field class in the Master’s and Doctorate in Geography course, which took place in July 2019, on the triple border, Brazil, Paraguay and Argentina. For this, a route and a script for the observations in specific places were elaborated, i- Pedro Ramalho settlement, ii- Maká community and iii- Guarani community. Cultural diversity and the relationship of interaction between ethnic groups were observed in the reports made by local residents, who were willing to tell their stories. It was also observed the diversity of characteristics that frontier spaces can offer when there are different behaviors in the developed ethnic relations.